Extraction and Purification of Laccases from Rice Stems - Chenna Swetha; Padubidri Shivaprasad (Bio-Protocol, 2019)
Laccases are found in cell walls of plants in very low amounts. This protocol provides an efficient method to purify laccases from rice stems. The method involves three steps: 1) Isolation of total protein from rice stems using buffers with high salt concentration to extract protein from cell walls; 2) Purification of laccases using concanavalin-A beads; and, 3) In-gel staining of laccases with 4-hydroxyindole. Concanavalin-A specifically binds to internal or non-reducing terminal α-D-mannosyl and α-D-glucosyl groups found in glycoproteins and glycolipids. Laccases being glycoproteins binds to concanavalin-A during purification process and eluted with mannose.